Penentuan Ukuran Lot Gabungan Untuk Pembeli Tunggal Dan Pemasok Tunggal Mempergunakan Pendekatan Vendor Managed Inventory-Consignment (VMI-C) - Docki Saraswati; Rahmi Maulidya; Mira Kurniasari (JURNAL TEKNIK INDUSTRI, 2011)
In fullfilmen the needs of raw materials partially, the buyer determines the amount of raw material ordered and the supplier send the appropriate amount of raw materials are ordered. These relationships often lead to a mismatch of needs raw materials by the number of available raw materials suppliers in the inventory purchases that result in higher costs of raw materials and the total cost of inventory. Therefore there is need for a policy that can control the system in an integrated supply of raw materials. The study begins with the determination of lot size by the buyer. Furthermore, the determination of lot size is determined by the supplier with approaches vendor-managed inventory (VMI). In this case the supplier to supervise the inventory status of the buyer, so buyers do not need to make the ordering process. At VMI with consignment approach (VMI-C) the buyer is not burdened with the cost savings, due to the transfer of ownership of raw materials occurs when raw materials used in the production floor. Based on calculations with observational data obtained on an approach that VMI and VMI-C total cost of inventory buyers and suppliers can deliver better results than not applying both approaches.